The Relationship Between the Jakarta Cardiovascular Score and Physical Activity: Screening of Cardiovascular Risk Factors in Older Adults - Citra Kiki Krevani Citra; Restu Restu Restu; Wahyudi Firmana Wahyudi; Rusdy Kamal Rusdy; Fikri Satria Fikri; Jolatuvel Bahana Jolatuvel; Najmi Ilal Hayati Najmi Ilal; Hajar Nurfa Jirin Hajar Nurfa (Frontiers on Healthcare Research, 2026)
Background: Cardiovascular disease (CVD) remains a leading cause of morbidity and mortality worldwide, including in Indonesia, where low physical activity is a major modifiable risk factor. The Jakarta Cardiovascular Score (JAKVAS) was developed as a local modification of the Framingham Risk Score to better represent Indonesian populations by including physical activity as a variable. However, the quantitative relationship between physical activity level and JAKVAS has not been well established. Methods: This cross-sectional analytical study involved 21 adult participants who took part in a community health screening. Data were collected through structured questionnaires covering JAKVAS components and the International Physical Activity Questionnaire (IPAQ). Physical activity was classified into low–moderate and high categories. Data were analyzed using independent t-test or Mann–Whitney test according to data distribution, with a significance level of p < 0.05. Results: Participants with high physical activity were predominantly male (83.3%; p = 0.003). No significant differences were observed in body mass index, blood pressure, or blood glucose levels. Smoking status (p = 0.003) and menopausal status (p = 0.003) were significantly associated with physical activity, whereas hypertension and diabetes mellitus were not. The median JAKVAS score was higher in the low–light activity group (median = 6; range 0–15) than in the moderate–vigorous group (median = 4; range 1–8; p = 0.066), indicating a trend toward lower cardiovascular risk with higher physical activity levels. Conclusion: Higher physical activity levels tended to correlate with lower cardiovascular risk scores based on JAKVAS, though not statistically significant. Promoting physical activity remains a key preventive strategy against cardiovascular disease in the community.